Answer:
c (2,3,-2)
Explanation:
3x+y+z = 7
x+3y-z =13
y = 2x-1
Add the first two equations together to eliminate z
3x+y+z = 7
x+3y-z =13
----------------------
4x+4y = 20
Divide by 4
4x/4 + 4y/4 = 20/4
x+y = 5
We know y = 2x-1. substitute this into the equation
x+ (2x-1) = 5
Combine like terms
3x-1 =5
Add 1 to each side
3x-1+1 =5+1
3x=6
Divide by 3
3x/3 = 6/3
x=2
Now we can find y
y = 2x-1
y = 2(2)-1
y =4-1
y= 3
We know x and y, now we need to find z
3x+y+z = 7
3(2) +3 +z = 7
6+3+z =7
9+z=7
Subtract 9 from each side
(-9+z =7-9
z=-2
So x=2,y=3 =-2
(2,3,-2)